SAT0323 Resveratrol, a Sirtuin-1 (HDAC 3) Activator, Increases IL-6 Production by PBMC of Patients with Knee Osteoarthritis. (23rd January 2014) - Wendling, D.; Godfrin-Valnet, M.; Khan, K. A.; Guillot, X.; Abbas, W.; Prati, C.; Cedoz, J.-P.; Baud, L.; Herbein, G.
Abstract : Background: Sirtuin 1 (Sirt1) is a nuclear enzyme from the class 3 histone deacetylases (HDACs) modulating gene expression, involved in the regulation of diverse biological processes (cell survival, apoptosis, gluconeogenesis, adipogenesis, lipolysis), local and systemic inflammation, as well as in bone and cartilage remodeling. Objectives: The main objective of the study was to evaluate Sirt1 activity in PBMC by venous blood aspiration in osteoarthritis (OA) patients, compared to those of control patients, and to analyze the relationship between Sirt1 activity and production of mediators of inflammation and cytokines (TNFalpha, IL-6, IL-8) by the cells after ex vivo treatment with a Sirtuin activator, resveratrol. Methods: A prospective and comparative monocentric study was performed in order to compare the activity of Sirt1 in patients with osteoarthritis and controls. OA was defined according to the ACR criteria, with radiological grading (K-L); symptoms were quantified with Lequesne's index. PBMC were isolated from venous blood, and Sirt1 activity was evaluated from cytoplasmic and nuclear compartments using a fluorometric assay (SIRT1 fluorimetric kit, BML-AK-555, Enzo Life Sciences, Villeurbanne, France) at the 15 minutes point. Culture supernatant levels of TNF alpha, IL-6, IL-8 were quantified before and after resveratrol (1 µmol and 5 µmol) ex vivo treatment, with commercial kits (Quantikine Kits, R&D Systems, Minneapolis, MN). Statistical analysis used Wilcoxon and t tests; significance : p less than 0.05. Results: Nineteen patients with symptomatic knee OA (age 64 ± 9 years, mean Lequesne's index : 8.4; grade II or III of the K-L classification) and 18 controls (age 54 ± 13 years) were included. No differences were found in cytoplasmic or nuclear Sirt1 activity between patients and controls. Cytoplasmic and nuclear Sirt1 activity were correlated in patients and controls. Sirt1 activity (nuclear and cytoplasmic) was correlated to baseline IL-6 (p = 0.002) and baseline TNF (p = 0.004), but not with IL-8. Sirt1 activity did not correlate with clinical activity (Lequesne's index) or biologic inflammation. After resveratrol treatment, no changes in TNF or IL-8 levels were found, but a significative, resveratrol-dose-dependent increase in IL-6 levels was demonstrated in OA patients (5.17 ± 0.89 pg/ml at baseline, 6, 72 ± 1.31 after 1 µmol ex vivo treatment, and 7.64 ± 1.35 after 5 µmol ex vivo treatment; p = 0.02), not found in controls. Conclusions: Sirt1 activity (cytoplasmic and nuclear) from PBMC was not different between OA patients and controls, nevertheless, ex vivo treatment of these PBMC with resveratrol, a Sirt1 activator, was unexpectedly associated with increased IL-6 levels in a dose-dependent relation only in OA patients, suggesting that IL-6 expression could be specifically regulated via Sirt1 in OA. Disclosure of Interest: None Declared